Protecting a Pict? further thoughts on the inscribed silver chape from St Ninian’s Isle, Shetland (Proceedings of the Society of Antiquaries of Scotland, 2020)
A detailed discussion of the inscription on the silver chape (NMS FC 282) discovered in 1958 as part of a large hoard of silver from the major early medieval ecclesiastical site on St Ninian’s Isle, Shetland (NGR: HU 3685 2090). Previous interpretations and a range of parallels are explored. A new interpretation of the inscription is proposed: that it contains a Pictish male personal name, Resad. This has implications for previous arguments in favour of an Anglo-Saxon origin for the metalwork. Features of the lettering previously interpreted as errors are instead argued to indicate familiarity with the type of cursive writing used on wax-tablets, rather than bookhand. It is argued that the inscription was designed and manufactured by a single literate artisan, possibly in an ecclesiastical workshop. Canmore ID 587